SISTEM PENUNJANG KEPUTUSAN PESERTA KURSUS UPTD BLK KAB. KUNINGAN DENGAN METODE PROFILE MATCHING BERBASIS WEB - Panji Novantara (Sistem Informasi Fakultas Ilmu Komputer Universitas Kuningan, 2018)
In accordance with the regulations set by the government in the process of graduation of course, needs criteria for determining the graduation of participants, especially in vocational information and communication technologies in the sub department office tools. In the process of determining graduation at UPTD BLK Kuningan, it needs a decision support system. One method that can be used for decision support system is using the Profile Matching. This method is chosen because it is able to select the best candidates from a number of course participants in Kuningan District, determining graduation course participants of UPTD BLK for assessment in determining the graduation, in this case the participants meant that the weight value for each attribute, such as aspects of intelligence and aspects of the work attitude, then it is conducted ranking process that will determine the optimal alternative, in this case is the best course participants.Keywords : SPK, Graduation Course Participants, Profile Matching Method